Derivation of physically motivated constraints for efficient interval simulations applied to the analysis of uncertain dynamical systems - Freihold, Mareile; Hofer, Eberhard P. (Zielona Góra: Uniwersytet Zielonogórski)
Interval arithmetic techniques such as VALENCIA-IVP allow calculating guaranteed enclosures of all reachable states of continuous-time dynamical systems with bounded uncertainties of both initial conditions and system parameters. Considering the fact that, in naive implementations of interval algorithms, overestimation might lead to unnecessarily conservative results, suitable consistency tests are essential to obtain the tightest possible enclosures.
Keywords: VALENCIA-IVP; consistency tests for the reduction of overestimation; identification of dynamical constraints; Hamiltonian systems; branch and prune algorithms